Modeling of Cu(II) adsorption from an aqueous solution using an Artificial Neural Network (ANN) - Khan T.; Manan T.S.B.; Isa M.H.; Ghanim A.A.J.; Beddu S.; Jusoh H.; Iqbal M.S.; Ayele G.T.; Jami M.S. (MDPI AG, 2023)
copper; sulfur; water; adsorption; algorithm; chemistry; diffusion; kinetics; molecular model; solution and solubility; thermodynamics; water pollutant; Adsorption; Algorithms; Copper; Diffusion; Kinetics; Models, Molecular; Neural Networks, Computer; Solutions; Sulfur; Thermodynamics; Water; Water Pollutants, Chemical